CALOHEE - Comparing Learning Outcomes in Higher Education in Europe - Assessment FrameworkHow to verify acquired learning outcomes - Alfredo Soeiro (2020)
DEPARTMENT OF MECHANICAL ENGINEERING ASSESSMENT IN ENGINEERING EDUCATION: A PEDAGOGICAL APPROACH AICTE APPROVED SHORT TERM TRAIINING PROGRAM (STTP) DETAILED SCHEDULE